A call for food system change (2020)
In shutting down entire societies, the COVID-19 pandemic has exposed the fundamental inequities and inadequacies of market-driven economies that prioritise profits over human welfare. Inequities show up in businesses that furlough employees while paying high salaries and bonuses to executives. They are also revealed by the dependence of food systems on poorly paid workers and cheap global supply chains. The COVID-19 crisis demonstrates how current food systems fail to protect populations from hunger and diet-influenced noncommunicable diseases and why the poor, disenfranchised, discriminated against, and chronically ill are those most vulnerable to this disease.